High-quality, conductive, and transparent Ga-doped ZnO films grown by atmospheric-pressure chemical-vapor deposition. Issue 2 (March 2015) - An, Ha-Rim; Ahn, Hyo-Jin; Park, Jeong-Woo
Abstract: Ga-doped zinc oxide (GZO) thin films were prepared by atmospheric-pressure chemical-vapor deposition (APCVD) using Ga injection rates over the range 70–150 sccm. When Ga atoms substituted the Zn atoms in the ZnO matrix, the electrical resistance of GZO thin films decreased, because the dopant atom generated one extra free electron. When the injection rate of Ga was 100 sccm, a very low resistivity of 2.03×10 −4  Ω·cm was realized; however, the resistivity was higher when the injection rate of Ga was over 100 sccm because of the agglomeration of Ga atoms in the ZnO matrix. All GZO thin films showed an optical transmittance of over 85%; in particular, when the Ga injection rate was 100 sccm, a superior figure-of-merit (FOM) of 7.58×10 −2  Ω −1 was found. GZO thin film prepared by APCVD could be a suitable transparent conductive oxide (TCO) material for variable optoelectronic devices.